Carvão ativado magnético para o tratamento de efluentes da indústria cafeeira - Silveira, Davi Batista (Universidade Federal de São Carlos, 2024)
As the planet’s largest natural resource, water plays a vital role in agriculture, industry, and housing. Although more than 70% of the Earth’s surface is covered by water, only 3% is freshwater. and less than 1% is suitable for drinking. In this context, the advancement of new technologies for treating wastewater from various sectors of society, such as the coffee agroindustry, is crucial for economic and environmental development. Coffee, being the second most consumed beverage globally, generates a significant amount of wastewater during its wet processing, resulting in the discharge of effluents containing high levels of organic compounds, such as phenolic compounds, which, if improperly discarded, can cause serious environmental damage. Among these compounds, chlorogenic acid stands out. Thus, this project aims to develop activated carbon with iron nanoparticles from sugarcane bagasse for the treatment of wastewater from the coffee agroindustry, as well as to study its morphological and physicochemical properties. For the preparation of activated carbon containing magnetic iron nanoparticles, sugarcane bagasse was used as the raw material, which was mixed with a polymer produced by a modified Pechini method. After mixing the sugarcane bagasse with the polymer, the material was subjected to physical activation. Thus, the combination of the adsorptive properties of activated carbon with the characteristics of the magnetic properties of the nanoparticles incorporated into the material may significantly simplify the separation and reuse of the adsorbent from the reaction environment. These operations are crucial since the economic viability of the process is directly linked to its regeneration and reuse. The results indicate that the material developed possesses an excellent adsorption capacity for the removal of phenol and chlorogenic acid used as a model molecule. Furthermore, It was determined that the method used to incorporate the iron nanoparticles, with magnetic properties, was successful, as evidenced by X-ray diffraction (XRD) analysis, high-resolution transmission electron microscopy (HR-TEM), and vibrating sample magnetometry (VSM).
Magnetic activated carbon for the treatment of effluents from the coffee industry.
Keywords: Carvão ativado; Compostos fenólicos; Bagaços de cana; Agroindustria do café; Activated carbon; Phenolic compounds; Sugarcane bagasse; Coffee agroindustry; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA